Kedudukan Duda Mulih Truna pada Perkawinan Nyentana di Banjar Pujung Kaja Desa Sebatu - Ni Luh Made Noviantini; I Ketut Sukadana; Diah Gayatri Sudibya (Fakultas Hukum, Universitas Warmadewa, 2020)
Balinese people adhere to the patrilineal family system. In Bali, the position of a man (purusa) is very important. There are several types of marriages in Bali, one of which is a Nyentana marriage. A man who carries out a Nyentana marriage is where a man is married by a woman and the marriage ceremony is held at the women's home. In Nyentana marriage there are many things that affect the occurrence of divorce, one of which is the problem of inheritance. Men who have been married in Nyentana marriage, then return to their original homes, no longer have the right to inherit in their original home because all of their inheritance rights have been lost since they legally carried out Nyentana marriages. Based on the above background, this study was conducted with the aim of outlining how the legal status of a Mulih Truna widower (Widower from Nyentana marriage) in his original home and how the right to inherit a Mulih Truna widower according to awig-awig (customary rules) in Banjar Pujung Kaja Sebatu Village. The method used in this legal research was empirical legal research methods. The results of this study indicateda man who returns to his original home after cessation will be called Mulih Trunawidower where the legal position in his home returns to being like a bujang (young man who has never been married) but does not reside as an heir again in his home. According to awig-awig in Banjar Pujung Kaja Sebatu Village, the right of inheriting a Mulih Trunawidower in his original home has been considered lost, and a Mulih Truna widower has been deemed to have left a kedaton (leaving all rights and obligations) in his home.